Historical review of the discovery of cadherin, in memory of Tokindo Okada. (26th December 2017) - Takeichi, Masatoshi
Abstract : The cadherin family of cell–cell adhesion molecules plays a pivotal role in animal tissue formation. Discovery of this molecular family can be traced back to some unexpected observations of strange cell behavior that were made around 1970 in the Kyoto University laboratory of Tokindo Okada, and then in the Department of Embryology at the Carnegie Institution of Washington (currently the Carnegie Institution for Science). This article looks back on these discoveries, and recalls how these observations led to the identification of important cell‐cell adhesion molecules known as cadherins. Abstract : This article looks back on the history of the discovery of cadherin, a family of cell–cell adhesion receptors important for tissue formation.